Actor Participation of Budgeting Policy Process in Banten, Indonesia - Delly Maulana; Endang Larasati; Sri Suwitri; Kismartini Kismartini (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
In actualizing the Regional Government Budget (APBD) as an instrument for the desired social changes and in accordance to the purpose for decentralization, there needs to be the involvement of the civil society, community groups, and other stakeholders in public management to influence the policy formulation process and policy implementation which could improve public services and public accountability. The purpose of the current study was to describe the process of formulating the budgeting policy and identifying and plotting the participation of a number of actors, both formal actors and informal actors, in the process of formulating the budgeting policy in the Banten Province Regional Government. The research method employed was a qualitative research method using the NVivo 12 Pro software application. A number of the current study’s findings which were related to the budgeting process were clearly linked to the actors’ political relation which would give rise to demands and requests in the form of actvity proposals. This process would also give rise to various compromises and bargaining between the actors involved, including the value system which influences it. Moreover, the process of formulating the budgeting policy in Banten Province Regional Government in 2018, both in planning and budgeting, were done only as a procedure but not yet substantively. Therefore, budgeting policy formulation process needs to prioritize more widespread public participation, especially in discussions and collecting input or information for the government, both directly or indirectly so that a transparent and accountable process is created.